Urban Water Quality and Fertilizer Ordinances: Avoiding Unintended Consequences: A Review of the Scientific Literature - George Hochmuth; Terril Nell; Jerry Sartain; J. Bryan Unruh; Chris Martinez; Laurie Trenholm; John Cisar (EDIS)
SL-283, a 31-page illustrated fact sheet by George Hochmuth, Terril Nell, Jerry Sartain, J. Bryan Unruh, Chris Martinez, Laurie Trenholm, and John Cisar, discusses the research behind turfgrass growth, biology and ecology, and soil nutrient cycling in the lawn. The unintended consequences of fertilizer ordinance restricted periods are presented to open dialogue among the stakeholders in the ordinance issue and to ensure that all information is presented to completely inform the policy-making process. Includes references. Published by the UF Department of Soil and Water Sciences, March 2009. Revised January 2011.